Do underwriters matter? The impact of the near loss of an equity underwriter - Anna Kovner (Federal Reserve Bank of New York, 2010)
The financial crisis provides a natural experiment for testing theoretical predictions of the equity underwriter's role following an initial public offering. Clients of Bear Stearns, Lehman Brothers, Merrill Lynch, and Wachovia saw their stock prices fall almost 5 percent, on average, on the day it appeared that their equity underwriter might collapse. Representing a loss in equity value of more than 3 billion, the decline was more than 1 percent lower than the conditional return predicted by a market model. The price impact was worse for companies with more opaque operations and fewer monitors, suggesting that underwriters play an important role in monitoring newly public companies. There is no evidence that the abnormal price decrease was related to the role of the underwriter as market maker or lender.
Keywords: G2; G24; G3; G30; G14; 330; Investment banking; financial crisis; IPOs; underwriting; event study